OXIDATIVE STRESS INDUCED BY CIPROFLOXACIN IN STAPHYLOCOCCUS AUREUS: MECHANISMS, IMPLICATIONS, AND POTENTIAL THERAPEUTIC STRATEGIES - Yaqoob Rahi, Alaa (PT. Antis International Publisher, 2025)
Objective: This study investigates the oxidative stress mechanisms induced by ciprofloxacin in Staphylococcus aureus, focusing on reactive oxygen species (ROS) generation, antioxidant responses, and cellular damage. Method: Using biochemical assays and gene expression analysis, we quantified ROS levels, lipid peroxidation, and protein carbonylation in a dose-dependent manner. Antioxidant enzyme activity and the bacterial SOS response were also examined to assess cellular defense mechanisms. Additionally, the potential protective effects of N-acetylcysteine (NAC) supplementation were evaluated. Results: Ciprofloxacin exposure significantly increased ROS production, leading to oxidative damage marked by elevated lipid peroxidation and protein carbonylation. Antioxidant enzyme activity was impaired, and the induction of the SOS response suggested an adaptive stress mechanism. NAC supplementation reduced ROS levels and partially restored bacterial viability, indicating a role for oxidative stress modulation in antimicrobial strategies. Novelty: This study provides novel insights into the oxidative stress-based bactericidal action of ciprofloxacin, demonstrating its impact on bacterial redox homeostasis and potential links to resistance mechanisms. The findings highlight the therapeutic potential of oxidative stress modulation to enhance antibiotic efficacy and mitigate resistance development in S. aureus.